Integration Of Innovation In Regional Potential-Based Development Planning in Accordance with RPJMD in Realizing Sustainable Development in The District North Labuhanbatu - Afif Prasetio Darsono; Cut Nuraini; Abdi Sugiarto (CV. Doki Course and Training, 2026)
This study aim to analyze the integration of innovation in development planning based on regional potential according to the RPJMD in North Sumatra Province, as well as to identify the obstacles and strategies to improve it. The research uses a qualitative approach with a case study, involving regional planning officials, academics, and the community as informants. Data was collected through in-depth interviews, participatory observation, and documentation, then analyzed thematically. The research results show that the level of innovation integration has developed, particularly in the use of information technology and electronic planning systems, but its implementation is still uneven. The main challenges include limitations in human resources, budget, regulations, social resistance, and limited infrastructure. The recommended strategies to improve planning effectiveness include strengthening HR capacity, utilizing technology, regulations that support innovation, participatory planning, synergy among stakeholders, as well as continuous monitoring and evaluation. This study contributes to the development of a more innovative, responsive, and sustainable RPJMD.